Formation of Sr2Si5N8:Eu2+ and Its Transformation to SrSi6N8:Eu2+ Controlled by Temperature and Gas Pressure. Issue 8 (19th May 2015) - Wu, Shin‐Mou; Hung, Hao‐En; Hsieh, Chi‐Hsing; Lin, Yin‐Chih; Wang, Li‐Chun; Tsai, Yi‐Ting; Lin, Chun Che; Liu, Ru‐Shi
Abstract : Firing temperature and gas pressure effect of synthesizing Sr2 Si5 N8 :Eu 2+ were investigated. The emission intensity is positively correlated with the firing temperature under 0.1 and 0.5 MPa gas pressure. The Sr2 Si5 N8 :Eu 2+ with the highest emission intensity was found at 1700°C and 1980°C under 0.1 and 0.5 MPa gas pressure, respectively. Although the maximum emission intensity of Sr2 Si5 N8 :Eu 2+ obtained under 0.5 MPa gas pressure condition is higher than that under 0.1 MPa. The Sr2 Si5 N8 :Eu 2+ synthesized under 0.5 MPa gas pressure in the temperature range from 1600°C to 1800°C have lower emission intensities than that synthesized under 0.1 MPa indicating that the melting of Sr3 N2 is an important step for the formation of Sr2 Si5 N8 :Eu 2+ . Moreover, the Sr2 Si5 N8 :Eu 2+ undergoes phase transition into SrSi6 N8 :Eu 2+ completely after elongating the heating duration to 6 h at 1980°C under 0.5 MPa gas pressure. The same feature was observed under 0.1 MPa gas pressure after firing 8 h at 1750°C. Different heating durations led to different degrees of phase transition.